Donor statin treatment protects against severe acute graft-versus-host disease after related allogeneic hematopoietic cell transplantation - Rotta, Marcello (American Society of Hematology, 2010)
We retrospectively analyzed outcomes among 567 patients with hematologic malignancies who had hematopoietic cell transplantation from human leukocyte antigen-identical sibling donors between 2001 and 2007 for a correlation between statin use and risk of graft-versus-host disease (GVHD). Compared with allografts where neither the donor nor recipient was treated with a statin at the time of transplantation (n = 464), statin use by the donor and not the recipient (n = 75) was associated with a decreased risk of grade 3-4 acute GVHD (multivariate hazard ratio, 0.28; 95% confidence interval, 0.1-0.9). Statin use by both donor and recipient (n = 12) was suggestively associated with a decreased risk of grade 3 or 4 acute GVHD (multivariate hazard ratio, 0.00; 95% confidence interval, undefined), whereas statin use by the recipient and not the donor (n = 16) did not confer GVHD protection. Risks of chronic GVHD, recurrent malignancy, nonrelapse mortality, and overall mortality were not significantly affected by donor or recipient statin exposure. Statin-associated GVHD protection was restricted to recipients with cyclosporine-based postgrafting immunosuppression and was not observed among those given tacrolimus (P = .009). These results suggest that donor statin treatment may be a promising strategy to prevent severe acute GVHD without compromising immunologic control of the underlying malignancy.